Hardware and software architecture for Plexil-based, simulation supported, robot automation (2016)
Some obsolete - but common - practices in the application of fertilizers and pesticides are causing serious environmental problems in Colombia; a situation that could be addressed by combining robotics and modern farming management principles, for example, the Precision Agriculture. This paper describes a novel application of Plexil - an experimental synchronous programming language developed by NASA-for robot automation in agriculture, supported by a simulation platform that allows quick prototyping of an automation plan, and a transparent integration of it on a physical robot. As a result, a methodology for evolutive robot development, and a case study with a real six-wheeled multipurpose agricultural robot are presented. Further applications of the simulation platform as a mean to easily introduce robotics engineers to alternative - and less error prone-programming models are also discussed.